Debate: can we achieve universal health coverage without a focus on disability? - Hannah Kuper; Johanna Hanefeld (BMC, 2018)
Abstract Background The achievement of Universal Health Coverage (UHC) is a key aim of the global health agenda, and an important target of the Sustainable Development Goals. There is increasing recognition that some groups may fall behind in efforts to achieve UHC, including the 1 billion people globally living with disabilities. A fundamental question for debate is - can UHC be achieved without the inclusion of people with disabilities? Main text People with disabilities are more likely to experience poor health. They will therefore have greater need for general healthcare services, as well as rehabilitation and specialist services, related to their underlying impairment. People with disabilities also frequently face additional difficulties in accessing healthcare, incur greater costs when seeking healthcare and often report experiencing worse quality services than others. As a consequence of these different challenges, people with disabilities face specific and added difficulties across three dimensions of UHC: coverage, access to services needed, and at reasonable cost. A focus on people with disabilities is therefore essential to achieving UHC, particularly since they constitute 15% of the global population. To ensure the realisation of UHC is inclusive of and addresses the needs of people with disabilities, health systems need to adapt. A twin-tracked approach is recommended, which means that there is a focus on including people with disabilities in mainstream services, as well as targeting them with specific services needed. There also must be efforts to improve the quality of services (e.g. through healthcare staff training) and enhance cost protection for people with disabilities (e.g. through social protection). A key challenge to changing UHC strategies to be more inclusive is the lack of evidence on what is needed and works, and more research is needed urgently on this topic. Conclusions It will be difficult to achieve UHC without a focus on people with disabilities. Changes made to improve coverage for people with disabilities will likely benefit a wider group, including older people, ethnic minorities, and people with short-term functional difficulties. Disability-inclusive strategies will therefore improve health system equity and ensure that we "Leave no one behind" as we move towards UHC.